Regulating party politics in the Western Balkans: the legal sources of party system development in Macedonia. Issue 3 (15th April 2016) - Casal Bértoa, Fernando; Taleski, Dane
Abstract : Party regulation in general and its systemic consequences in particular have not been a matter of concern for scholars until very recently. Despite recent efforts to study how political parties are regulated in post-authoritarian democracies and in conflict-prone societies, the question of how party legislation affects party formation and party system development in the Western Balkans still remains a mystery. Adopting a multi-disciplinary (that is, legal and political) approach, this article attempts to fill a gap in the literature by analysing how different party (finance) regulations shaped the party system in Macedonia, one of Europe's most recent (and under-researched) democracies, while controlling for changes in electoral regimes. There are two main findings. On the one hand, registration requirements had the strongest impact on the party system format, even when the electoral system pushed in the opposite direction. On the other, public funding, rather than "cartelizing" the system, mainly facilitated the survival of (both big and small) parties. Finally, the article also points to the need to explore the role of shadow financing and corruption when analysing the effects of party finance in new democracies.